A national quality improvement study identifying and addressing cancer screening deficits due to the COVID‐19 pandemic. Issue 11 (21st March 2022) - Joung, Rachel H.; Nelson, Heidi; Mullett, Timothy W.; Kurtzman, Scott H.; Shafir, Sarah; Harris, James B.; Yao, Katharine A.; Brajcich, Brian C.; Bilimoria, Karl Y.; Cance, William G.
Abstract : Background: Cancer‐related deaths over the next decade are expected to increase due to cancer screening deficits associated with the coronavirus disease 2019 (COVID‐19) pandemic. Although national deficits have been quantified, a structured response to identifying and addressing local deficits has not been widely available. The objectives of this report are to share preliminary data on monthly screening deficits in breast, colorectal, lung, and cervical cancers across diverse settings and to provide online materials from a national quality improvement (QI) study to help other institutions to address local screening deficits. Methods: This prospective, national QI study on Return‐to‐Screening enrolled 748 accredited cancer programs in the United States from April through June 2021. Local prepandemic and pandemic monthly screening test volumes (MTVs) were used to calculate the relative percent change in MTV to describe the monthly screening gap. Results: The majority of facilities reported monthly screening deficits (colorectal cancer, 80.6% [n = 104/129]; cervical cancer, 69.0% [n = 20/29]; breast cancer, 55.3% [n = 241/436]; lung cancer, 44.6% [n = 98/220]). Overall, the median relative percent change in MTV ranged from –17.7% for colorectal cancer (interquartile range [IQR], –33.6% to –2.8%), –6.8% for cervical cancer (IQR, –29.4% to 1.7%), –1.6% for breast cancer (IQR, –9.6% to 7.0%), and 1.2% for lung cancer (IQR, –16.9% to 19.0%). Geographic differences were not observed. There were statistically significant differences in the percent change in MTV between institution types for colorectal cancer screening ( P = .02). Conclusion: Cancer screening is still in need of urgent attention, and the screening resources made available online may help facilities to close critical gaps and address screenings missed in 2020. Lay Summary: Question: How can the effects of the coronavirus disease 2019 pandemic on cancer screening be mitigated? Findings: When national resources were provided, including methods to calculate local screening deficits, 748 cancer programs promptly enrolled in a national Return‐to‐Screening study, and the majority identified local screening deficits, most notably in colorectal cancer. Using these results, 814 quality improvement projects were initiated with the potential to add 70, 000 screening tests in 2021. Meaning: Cancer screening is still in need of urgent attention, and the online resources that we provide may help to close critical screening deficits. Abstract : A national Return‐to‐Screening quality improvement study including 748 cancer facilities has found that the majority have local screening deficits due to the COVID‐19 pandemic, most notably in colorectal cancer. Cancer screening is still in need of urgent attention, and the screening resources made available online may help to close critical gaps and address screenings missed in 2020.